Online travel purchase decision among youth traveller in Malaysia. - Azizul, Nur Erriena Sari; Azizan, Farah Lina; Ismail, Ismalaili (International Journal of Accounting, Finance and Business, 2025)
Previous studies have focus on online travel products but not service on the websites hence only one study focuses on online travel purchase decision of travel among youth consumer in Malaysia. Taking this into consideration, the present research hopes to further investigate and understand online travel purchase decision among youth travelers in Malaysia. This conceptual paper discusses the factors that influence online travel purchase decision among youth traveler in Malaysia. Specifically, the paper elaborates on the purpose relationship between website design, perceived risk, perceived usefulness, subjective norms and trust. Based on the extended discussion on relationships, the paper also provides a research framework for the online travel purchase decision for other researchers to expand in the future. This new framework has the potential to broaden everyone's perspective and comprehension of online travel purchase decisions. Tourism agencies and online travel shop can use online marketing strategy that will be suggested to improve their business and make better profit. With the understanding of consumer preferences and expectations, the travel companies will be able to design their marketing strategies properly and maintain the loyalty of their consumers when purchasing online. Besides contributing towards the literature on youth travelers purchase decisions, this paper will reinvigorate the factors of website design, perceived risk, perceived usefulness, subjective norms and trust towards the online travel purchase decision among youth travelers in Malaysia.